PEMBENTUKAN BAUKSIT DAN FERIT PADA PROFIL PELAPUKAN DI KABUPATEN LINGGA: FORMATION OF BAUXITE AND FERRITE IN WEATHERED PROFILES ON LINGGA REGENCY - Ronaldo Irzon (Buletin Sumber Daya Geologi, 2022)
Weathering could stimulate the formation of several economic deposits such as bauxite, ferrite, nickel, manganese, and ion-adsorption type REE. Lingga Regency is situated near the equator with a tropical climate that is vulnerable to weathering. The area is constituted of several Paleozoic rock units and is located near the Bentong-Raub Suture that sustains intensive weathering for a long time. This study aims to describe the geochemical characteristics of weathered rocks and the formation of weathering-related mineral deposits in the Lingga Regency. All samples are weathered based on LOI, CIA, and IOL parameters. The SiO2-Fe2O3T-Al2O3 triangular diagram shows that ferrite and bauxite are formed in totally four locations. The highest Al2O3 concentration of bauxite reaches 60%, while the highest Fe2O3T of ferrite is 69%. La/Y ratio defines that weathering happened in a basic environment, while Al/Ti ratio concludes that the studied samples are originated from felsic rock. REE in weathering profiles are more extractable than those in igneous rocks, but the composition in this study is not attractive for further exploitation as they are range in low to medium concentrations. Further research is required to quantify bauxite and ferrite resources and reserves in Lingga Regency.